INSTRUCTING LANGUAGE LEARNING STRATEGIES TO PROMOTE AUTONOMOUS LEARNING - Konder Manurung (Universitas Katolik Indonesia Atma Jaya, 2005)
The paper discusses the effects of language learning strategy instruction on the improvement of the four language skills at tertiary education level. The focus of the discussion reflects two main points. The first relates to the effect of instruction in the use of language learning strategies prior to undertaking autonomous language learning in a self-access center on the improvement of the four language skills, and the second relates to the language learning strategies used in the self-access center where autonomous language learning takes place. The paper argues that language learning strategies instruction promotes autonomous language learning mode and contributes to the improvement of both the productive and the receptive skills. It is also evident that there are some other language learning strategies used during the autonomous learning in the self-access center other than those identified and used in foreign language learning. Practical application of autonomous learning mode in the self-access center in relation to the teaching of English to non-language departments at tertiary education level is also suggested. Keywords: language learning strategy instruction, autonomouslanguage learning, self-access center